Shennongjia–Wushan Mountains—One cryptic glacial refugium introduced by the phylogeographical study of the Geometridae moth Ourapteryx szechuana Wehrli - Cheng, Rui; Han, Hongxiang; Xue, Dayong; Zhu, Chaodong; Jiang, Nan (Ecology and evolution, 2021)
The origin and evolution of biodiversity in the Shennongjia and Wushan Mountains, located in central China, are little known. In this study, we used Ourapteryx szechuana, which is widely distributed in China and northern Nepal, to explore whether these mountains acted as glacial refugia during climate oscillations of the Quaternary. In total, 192 samples of O. szechuana were collected throughout much of the distribution range. Phylogenetic analysis, molecular dating, demographic history reconstructions, and MAXENT were used to investigate the evolutionary history and differentiation mechanisms and predict the potential species distributions during four different periods. The phylogenetic tree and the star‐like median‐joining network strongly supported two reciprocally monophyletic and allopatric lineages. Lineage I was restricted to the Shennongjia and Wushan Mountains. The divergence time of O. szechuana from its sister species O. thibetaria was approximately 1.94 Ma. The differentiation processes of the two intraspecific lineages occurred at approximately 0.47 Ma. The demographic history reconstruction and the ecological niche model suggested that Lineage II experienced an expansion after the LGM (Last Glacial Maximum), whereas Lineage I did not experience any expansion. Our results suggested the Naynayxungla glaciation promoted the divergence of the two lineages by restricting them to different refugia. The valleys of the Shennongjia–Wushan Mountains may have kept stable and warm (thus ice‐free) environments during Quaternary glaciations, allowing this region to act as a glacial refugia. Our studies show that the Shennongjia and Wushan Mountains are likely to be important but little studied glacial refugia for the insect and thus worthy of more attention. The Naynayxungla Glaciation promoted the divergence of the two lineages by restricting them to different refugia. The Shennongjia and Wushan Mountains are one important and easily neglected refugia for the insect groups and are worthy of more attention.